'Damned if you do and damned if you don't': a framework for examining double binds in public service organizations. Issue 7 (3rd July 2022) - Røhnebæk, Maria Taivalsaari; Breit, Eric
ABSTRACT: A key challenge for contemporary public service organizations is the requirement to incorporate different, at times conflicting, demands into their operations. Such demands and the organizational challenges they impose have been described in theories of institutional complexity, organizational paradox(es) and conflicting public values. In this paper, we complement these existing theories by developing an analytical framework based on the 'double bind' theory. The framework enables understandings of conflicting demands stemming from double communication and elusive mixed messages. We demonstrate the usefulness of the double bind framework by examining the Norwegian Labour and Welfare Administration.